The effect of green and red light spectra and their intensity on the oxidative stress and non-specific immune responses in gold-striped amberjack, Seriola lalandi. Issue 4 (3rd July 2016) - Choi, Young Jae; Choi, Ji Yong; Yang, Sang-Geun; Kim, Bong-Seok; Choi, Cheol Young
Abstract: The present study examined the effects of different light spectra (red and green light-emitting diodes [LEDs]) and light intensities (0.3 and 0.5 W m −2 ) on antioxidant systems (superoxide dismutase, H2 O2 and lipid peroxidation) and immunity (lysozyme, melatonin and endorphin) in gold-striped amberjack, Seriola lalandi. In groups exposed to green LED, the levels of antioxidant enzyme were significantly lower than in the control, whereas the levels of immune-related parameters were significantly higher compared to other groups. The levels of antioxidant enzyme in individuals exposed to red light increased with increasing light intensity, whereas these levels were not correlated to the intensity of green light and were increased even at low light intensity. These results indicate that exposure to low-intensity green light accelerates the antioxidant system and immune system.